Influence of Fabrication Route and Copper Content on Nature and Kinetics of 475 °C- Embrittlement in Cu-Containing Super Duplex Stainless Steels - Hosseini, Vahid A.; Thuvander, Mattias; Lindgren, Kristina; Oliver, James; Folkeson, Nicklas; Gonzalez, Daniel; Cengiz, Sezgin (Wiley-V C H Verlag Gmbh, 2023)
The influence of hot-rolling, hot isostatic pressing (HIP), welding, as well as copper content on 475 degrees C-embrittlement is studied in super duplex stainless steels. The as-received samples are solution annealed and quenched. Then, to study the kinetics and nature of phase transformations during fabrication, the samples are aged for a very short duration of 5 min at 475 degrees C. Atom probe tomography results reveal that the processes involving more plastic deformation such as hot rolling and HIP accelerate chromium and iron phase separation and cause precipitation of copper-rich particles (CRPs) in ferrite, resulting in significant toughness loss. In contrast, the weld does not show a high level of chromium and iron phase separation or CRPs precipitation, preserving its toughness after the short aging. The experiment and the inverse interdiffusion calculations reveal that raising the copper content slow down chromium and iron phase separation but significantly increase the CRP number density and decrease the toughness of the HIPed material. Precipitation simulation of CPRs show that the model must be modified based on each processing condition. It is concluded that hot rolling and HIP accelerate 475 degrees C-embrittlement, which cannot be prevented by raising the copper content.
Keywords: Cu-rich particle precipitation; Fe and Cr phase separation; simulations; super duplex stainless steels; 475 degrees C; embrittlement